Implementation of A Geographically Integrated On-Demand Computer Service System Using the KNN Method - Wardana, Hafiq Ibnu; Putri, Astrid Novita (Jurnal Teknologi Informatika dan Komputer, 2025)
The rapid development of information and communication technology has driven significant changes in various fields, including the service sector. Internet-based digital services provide quick and easy access to all needs, such as ordering transportation, food, or even services. On-demand services are services based on customer demand (Anjani & Sujarwo, 2023). This research aims to develop a web-based on-demand computer service system integrated with geographic location using the K-Nearest Neighbor (KNN) algorithm. Difficult access for customers with limited mobility, the lack of location-based partner distribution, and the manual partner search process remain major challenges in conventional computer service. The system was developed using Laravel as the backend framework and MySQL as the database processor, using the KNN method to measure the closest distance between the user's location and the partner based on latitude and longitude coordinates. The results show that the system can automatically provide information in the form of recommendations for the nearest technician partner, which can increase service time efficiency and make it easier for consumers to access professional computer service. A user-friendly interface and a simple ordering process can enhance user experience. This study recommends further system development by integrating digital payment methods and conducting more detailed classification accuracy testing to improve the quality of the service system's recommendations.